Sensorial analysis of a functional beverage based on vegetables juice - Profir, Alina G.; Vizireanu, Camelia (Acta Biologica Szegediensis, 2013)
Functional food products have become an important segment of food industry. They have been defined as products that provide physiological benefits or reduce the risk of chronic disease beyond primary nutritional functions. The continuous growth of functional food market is a consequence of the increasing interests for products that offering health benefits. The elaborations of new functional products lead to an increasing competition so that the consumer acceptance of the new products is important. The sensorial analysis can provide essential information to obtain a good understanding of consumer food choice. Due to the bioactive compounds contained, vegetables juice can be a convenient medium for the development of a functional beverage. The present study is focused on the consumer acceptance of a fermented juice made from beetroot, carrot and celery. This juice has been inoculated with three probiotic strains: Lactobacillus acidophilus, Lactobacillus casei and Saccharomyces boulardii. After lactic fermentation, the functional beverage has been evaluated by trained panelists. All the data has been analyzed using Senpaq statistical software.